2005
DOI: 10.1002/dvdy.20515
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mouse dchs1, fjx1, and fat‐j suggests conservation of the planar cell polarity pathway identified in drosophila

Abstract: The dachsous (ds), fat (ft), and four-jointed (fj) genes have been identified in Drosophila as part of a signaling pathway that regulates planar cell polarity (PCP). A homologous PCP signaling pathway has also been identified in vertebrates, but nothing is known thus far about the conservation of Ds/Ft/Fj signaling. Here we analyzed and compared for the first time the expression patterns of all ds, ft and fj homologs in the mouse. During embryogenesis, expression analysis was performed by RNA in situ hybridiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 42 publications
5
93
0
1
Order By: Relevance
“…In mammals, four types of Ft proteins, namely Ft1, Ft2, Ft3, and Ft4, have been identified (Rock et al, 2005;Tanoue and Takeichi, 2005). Among them, Ft4 is the vertebrate counterpart of Drosophila Ft based on their sequence similarity (Rock et al, 2005;Matakatsu and Blair, 2006).…”
Section: Relationship Of the Ds-ft Signaling Pathway With Vertebrate mentioning
confidence: 99%
See 3 more Smart Citations
“…In mammals, four types of Ft proteins, namely Ft1, Ft2, Ft3, and Ft4, have been identified (Rock et al, 2005;Tanoue and Takeichi, 2005). Among them, Ft4 is the vertebrate counterpart of Drosophila Ft based on their sequence similarity (Rock et al, 2005;Matakatsu and Blair, 2006).…”
Section: Relationship Of the Ds-ft Signaling Pathway With Vertebrate mentioning
confidence: 99%
“…Among them, Ft4 is the vertebrate counterpart of Drosophila Ft based on their sequence similarity (Rock et al, 2005;Matakatsu and Blair, 2006). Recently, Saburi et al (2008) reported phenotypes of Ft4-null mice.…”
Section: Relationship Of the Ds-ft Signaling Pathway With Vertebrate mentioning
confidence: 99%
See 2 more Smart Citations
“…Drosophila Fat (dFat) was first identified as a putative tumour suppressor gene involved in planar cell polarity and tissue size regulation via the Hippo signalling pathway (Mahoney et al, 1991;Matakatsu and Blair, 2004;Willecke et al, 2006). Of the four vertebrate orthologues of dFat, Fat4 (also called FatJ) shows the greatest homology to dFat (Matakatsu and Blair, 2006) and is expressed in a variety of tissues with active PCP signalling (Rock et al, 2005), including the kidney, where loss of Fat4 alters orientated cell divisions and leads to kidney dysfunction. Fat4 additionally plays a role within the CNS: loss of Fat4 expression in the cerebellum reduces the apical membrane compartment, suggesting a role in apical-basal polarity (Ishiuchi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%